1990
DOI: 10.1093/jpepsy/15.3.309
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral Approach to Increasing Calorie Consuption in Children With Cystic Fibrosis

Abstract: To increase calorie consumption of 5 mildly malnourished children with cystic fibrosis (CF), intervention was implemented in multiple baseline fashion across snack and three meals. Intervention involved nutritional education establishing gradually increasing calories goals, teaching parents contingency management strategies, and a reward system for achieving calorie goals. Following 6 treatment sessions, the children's calorie intake increased across meals and total calorie intake was 25 to 43% above baseline.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 0 publications
6
49
0
Order By: Relevance
“…Because of the potential health implications of poor parent-child mealtime interactions in families of young children with type 1 diabetes, it is likely that these families may benefit from behavioral-based interventions to improve mealtimes. Within the behavioral science literature, research has demonstrated that common disruptive child behaviors can be effectively reduced by establishing specific rules and consequences for mealtimes and teaching parents behavioral strategies for meals (16). We report on the relationships between mealtime behaviors and children's dietary adherence and blood glucose control in a sample of young children with type 1 diabetes.…”
Section: Mealtime Characteristicsmentioning
confidence: 99%
“…Because of the potential health implications of poor parent-child mealtime interactions in families of young children with type 1 diabetes, it is likely that these families may benefit from behavioral-based interventions to improve mealtimes. Within the behavioral science literature, research has demonstrated that common disruptive child behaviors can be effectively reduced by establishing specific rules and consequences for mealtimes and teaching parents behavioral strategies for meals (16). We report on the relationships between mealtime behaviors and children's dietary adherence and blood glucose control in a sample of young children with type 1 diabetes.…”
Section: Mealtime Characteristicsmentioning
confidence: 99%
“…Results demonstrated significant improvement in treatment adherence compared to standard care and education only groups. Stark and colleagues demonstrated significant improvements in dietary adherence (i.e., calorie consumption) in cystic fibrosis baseline to post-treatment 15,16 , and at two-year follow up 17,18 using group-based behavioral intervention. The same treatment approach was used to increase dietary calcium intake in children with Juvenile Rheumatoid Arthritis (JRA) and IBD.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies by Stark and colleagues (Stark, Bowen, Tyc, Evans, & Passero, 1990;Stark et al, 1993;Stark et al, 1996) shows that a combined behavioral and nutrition treatment for 4-to 11-year-old children with CF can lead to increased calorie intake and weight gain. The nutrition component of the intervention included setting specific calorie goals and targeting one meal at a time.…”
mentioning
confidence: 99%